Advances in drug delivery via electrospun and electrosprayed nanomaterials - Zamani M; Prabhakaran MP; Ramakrishna S (International Journal of Nanomedicine, 2013)
Maedeh Zamani,1 Molamma P Prabhakaran,2 Seeram Ramakrishna1,21Department of Mechanical Engineering, 2Center for Nanofibers and Nanotechnology, National University of Singapore, SingaporeAbstract: Electrohydrodynamic (EHD) techniques refer to procedures that utilize electrostatic forces to fabricate fibers or particles of different shapes with sizes in the nano-range to a few microns through electrically charged fluid jet. Employing different techniques, such as blending, surface modification, and coaxial process, there is a great possibility of incorporating bioactive such molecules as drugs, DNA, and growth factors into the nanostructures fabricated via EHD techniques. By careful selection of materials and processing conditions, desired encapsulation efficiency as well as preserved bioactivity of the therapeutic agents can be achieved. The drug-loaded nanostructures produced can be applied via different routes, such as implantation, injection, and topical or oral administration for a wide range of disease treatment. Taking advantage of the recent developments in EHD techniques like the coaxial process or multilayered structures, individually controlled delivery of multiple drugs is achievable, which is of great demand in cancer therapy and growth-factor delivery. This review summarizes the most recent techniques and postmodification methods to fabricate electrospun nanofibers and electrosprayed particles for drug-delivery applications.Keywords: electrospinning, electrospraying, gene delivery, growth-factor delivery, cancer therapy, wound dressing